The plant-derived triterpenoid, cucurbitacin B, but not cucurbitacin E, inhibits the developmental transition associated with ecdysone biosynthesis in Drosophila melanogaster. (October 2021) - Toyofuku, Miwako; Fujinaga, Daiki; Inaba, Kazue; Funahashi, Tomoki; Fujikawa, Yuuta; Inoue, Hideshi; Kataoka, Hiroshi; Niwa, Ryusuke; Ono, Hajime
Graphical abstract: Highlights: Cucurbitacin B inhibits larval molting under restriction of sterol availability. Developmental delay by cucurbitacin B is rescued by ecdysone administration. Cucurbitacin B inhibits ecdysone production in the prothoracic gland in vitro . Cucurbitacin E does not inhibit ecdysone production in the prothoracic gland. Abstract: In insects, some sterols are essential not only for cell membrane homeostasis, but for biosynthesis of the steroid hormone ecdysone. Dietary sterols are required for insect development because insects cannot synthesize sterols de novo . Therefore, sterol-like compounds that can compete with essential sterols are good candidates for insect growth regulators. In this study, we investigated the effects of the plant-derived triterpenoids, cucurbitacin B and E (CucB and CucE) on the development of the fruit fly, Drosophila melanogaster . To reduce the effects of supply with an excess of sterols contained in food, we reared D . melanogaster larvae on low sterol food (LSF) with or without cucurbitacins. Most larvae raised on LSF without supplementation or with CucE died at the second or third larval instar (L2 or L3) stages, whereas CucB-administered larvae mostly died without molting. The developmental arrest caused by CucB was partially rescued by ecdysone supplementation. Furthermore, we examined the effects of CucB on larval-prepupal transition by transferring larvae from LSF supplemented with cholesterol to that with CucB just after the L2/L3 molt. L3 larvae raised on LSF with CucB failed to pupariate, with a remarkable developmental delay. Ecdysone supplementation rescued the developmental delay but did not rescue the pupariation defect. Furthermore, we cultured the steroidogenic organ, the prothoracic gland (PG) of the silkworm Bombyx mori, with or without cucurbitacin. Ecdysone production in the PG was reduced by incubation with CucB, but not with CucE. These results suggest that CucB acts not only as an antagonist of the ecdysone receptor as previously reported, but also acts as an inhibitor of ecdysone biosynthesis.